Prevalence and Significance of Impaired Microvascular Tissue Reperfusion Despite Macrovascular Angiographic Reperfusion (No-Reflow). (22nd February 2022) - Ng, Felix C.; Churilov, Leonid; Yassi, Nawaf; Kleinig, Timothy John; Thijs, Vincent; Wu, Teddy; Shah, Darshan; Dewey, Helen; Sharma, Gagan; Desmond, Patricia; Yan, Bernard; Parsons, Mark; et al.
Abstract : Background and Objectives: The relevance of impaired microvascular tissue-level reperfusion despite complete upstream macrovascular angiographic reperfusion (no-reflow) in human stroke remains controversial. We investigated the prevalence and clinical-radiologic features of this phenomenon and its associations with outcomes in 3 international randomized controlled thrombectomy trials with prespecified follow-up perfusion imaging. Methods: In a pooled analysis of the Extending the Time for Thrombolysis in Emergency Neurological Deficits–Intra-Arterial (EXTEND-IA; ClinicalTrials.gov NCT01492725), Tenecteplase Versus Alteplase Before Endovascular Therapy for Ischemic Stroke (EXTEND-IA TNK; NCT02388061), and Determining the Optimal Dose of Tenecteplase Before Endovascular Therapy for Ischaemic Stroke (EXTEND-IA TNK Part 2; NCT03340493) trials, patients undergoing thrombectomy with final angiographic expanded Treatment in Cerebral Infarction score of 2c to 3 score for anterior circulation large vessel occlusion and 24-hour follow-up CT or MRI perfusion imaging were included. No-reflow was defined as regions of visually demonstrable persistent hypoperfusion on relative cerebral blood volume or flow maps within the infarct and verified quantitatively by >15% asymmetry compared to a mirror homolog in the absence of carotid stenosis or reocclusion. Results: Regions of no-reflow were identified in 33 of 130 patients (25.3%), encompassed a median of 60.2% (interquartile range 47.8%–70.7%) of the infarct volume, and involved both subcortical (n = 26 of 33, 78.8%) and cortical (n = 10 of 33, 30.3%) regions. Patients with no-reflow had a median 25.2% (interquartile range 16.4%–32.2%, p < 0.00001) relative cerebral blood volume interside reduction and 19.1% (interquartile range 3.9%–28.3%, p = 0.00011) relative cerebral blood flow reduction but similar mean transit time (median −3.3%, interquartile range −11.9% to 24.4%, p = 0.24) within the infarcted region. Baseline characteristics were similar between patients with and those without no-reflow. The presence of no-reflow was associated with hemorrhagic transformation (adjusted odds ratio [aOR] 1.79, 95% confidence interval [CI] 2.32–15.57, p = 0.0002), greater infarct growth (β = 11.00, 95% CI 5.22–16.78, p = 0.00027), reduced NIH Stroke Scale score improvement at 24 hours (β = −4.06, 95% CI 6.78–1.34, p = 0.004) and being dependent or dead at 90 days as assessed by the modified Rankin Scale (aOR 3.72, 95% CI 1.35–10.20, p = 0.011) in multivariable analysis. Discussion: Cerebral no-reflow in humans is common, can be detected by its characteristic perfusion imaging profile using readily available sequences in the clinical setting, and is associated with posttreatment complications and being dependent or dead. Further studies evaluating the role of no-reflow in secondary injury after angiographic reperfusion are warranted. Classification of Evidence: This study provides Class II evidence that cerebral no-reflow on CT/MRI perfusion imaging at 24 hours is associated with posttreatment complications and poor 3-month functional outcome.